Coronary artery spasm and impaired myocardial perfusion in patients with ANOCA: Predictors from a multimodality study using stress CMR and acetylcholine testing. (15th November 2021) - Pirozzolo, Giancarlo; Martínez Pereyra, Valeria; Hubert, Astrid; Guenther, Fabian; Sechtem, Udo; Bekeredjian, Raffi; Mahrholdt, Heiko; Ong, Peter; Seitz, Andreas
Abstract: Background: Functional coronary disorders such as coronary spasm and microvascular dysfunction (including microvascular spasm and impaired microvascular dilatation) are frequent findings among patients with angina and non-obstructed coronary arteries (ANOCA). In this study, we investigated a potential association of coronary spasm and myocardial perfusion abnormalities as well as predictors of such functional coronary disorders in ANOCA patients using a multimodality diagnostic strategy including adenosine stress CMR and intracoronary acetylcholine testing. Methods: We enrolled 129 patients with ANOCA who underwent acetylcholine testing and adenosine stress perfusion CMR. Patients were allocated to 3 groups according to their spasm testing result with regard to standardized COVADIS criteria: 1) epicardial spasm, 2) microvascular spasm, and 3) no spasm. The myocardial perfusion reserve index (MPRI) was semiquantitatively determined from adenosine stress perfusion CMR. Multivariate regression analyses were performed to identify predictors of coronary functional disorders. Results: Patients with epicardial spasm had lower MPRI than patients without, whereas MPRI was preserved in patients with microvascular spasm. Multivariate analyses revealed age, previous myocardial infarction, LVEF and epicardial spasm as independent predictors of diminished MPRI, whereas previous PCI was associated with epicardial spasm, and female sex was a strong predictor of microvascular spasm. Conclusions: Our results demonstrate coexistence of different functional coronary disorder endotypes involving the macro- and microvascular level of the coronary circulation in patients with ANOCA. We demonstrate that epicardial spasm is associated with diminished myocardial perfusion reserve and report further predictors of coronary functional disorders. Highlights: Assessment of vasomotor dysfunction by CMR and acetylcholine testing is feasible. Coronary artery spasm and impaired microvascular vasodilation coexist. Age and previous myocardial infarction are independent predictors of low MPRI. Epicardial spasm is associated with low MPRI. Prior PCI is predictive for epicardial spasm and female sex for microvascular spasm.